DESAIN SISTEM MONITORING CONTROL AND SURVEILLANCE NASIONAL DALAM RANGKA PEMBANGUNAN KELAUTAN INDONESIA (National Monitoring, Control and Surveillance Design System for Marine Development in Indonesia) - Harmin Sarana; John Haluan; Daniel R. Monintja; Tommy H. Purwaka; Hartrisari Hardjomidjojo (Buletin PSP, 2007)
Indonesia, an archipelago of 17,508 islands has an abundant of marine resources and also strategic position in international sea-traffic. MCS should be applied to protect Indonesia from illegal activities at the sea. The purpose of this research is to design a national monitoring control and surveillance system in developing Indonesian maritime. Benchmarking analysis was chosen as the preferred analysing method to compare the Indonesian MCS activities with 24 other countries. In order to determine the key factors of Indonesian MCS system, an expert survey was performed. The analysis result shows that the Indonesian MCS activities still operates in a low level compared to the MCS activities of many countries, such as Canada, Australia, and America. Thus, in order to reach a more preferred level, lndonesia has to improve their MCS operation base and furthermore also improve their MCS performance. In order to improve the Indonesian MCS system, factors such as legislation and permission should be more heavily considered, while the performance level of other factors relating to MCS should also be increased. Further research conducted through the SWOT and statistical analysis is still needed in order to determine the system development model of Indonesian MCS.Key words: MCS, benchmarking analysis, design system, prospective analysis.